Annual variation of the terrestrial macrofauna during autumn period in a forest ecosystem of Galicica National Park - Sapkarev, Jonče (Macedonian Journal of Ecology and Environment, 1993)
The article dipicts the ecological conditions existing in the soil of examined forest ecosystem, gives the structure of the terrestrial macrofaun a and its density of community of certain animal groups, as well as annual variation and vertical distribution of their population's densities in autumn period during 1979, 1980 and 1981.